(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Thanks to the latest achievements of AI and neural machine translation (MT) technologies, machine support in translation has been used every day in many fields of work and life. Today, MT can increase productivity in technical texts translated by people without influencing the final quality of the product given certain conditions. However, it is commonly believed that MT cannot compete with human translation of literary or more creative texts precisely because of the machine has lack of creativity. In this article we exlore readers’ narrative engagement in texts translated using different modalities such as machine translation, human translation.